Serum miR-125b levels associated with epithelial ovarian cancer (EOC) development and treatment responses. Issue 1 (1st January 2020) - Chen, Zhonghua; Guo, Xiaoli; Sun, Shukai; Lu, Caixia; Wang, Liming
ABSTRACT: Downexpression of miRs was associated with tumor development, progression, and metastasis. This study explored the serum levels of miR-125b in patients with epithelial ovarian cancer (EOC) and to assess its diagnostic value and monitor treatment responses for patients with EOC. A total of 379 individuals were recruited and assigned to the study groups. RT-qPCR analysis was performed to conﬁrm the association of serum miR-125b levels with tumor stages and treatment responses. The median serum levels of miR-125b in patients with EOC were signiﬁcantly lower than that of other controls (P < 0.0001). Serum miR-125b in patients with high FIGO stage (III+IV), lymph node metastasis, and chemoresistance were lower than that in patients with early-stage (stage I+ II; P < 0.001), without lymph metastasis (p = 0.032) and chemosensitivity (P < 0.001). Low levels of miR-125b had a poor prognosis in patients with EOC. Using a median value of 0.748 to separate EOC from other controls, the sensitivity and speciﬁcity reached 0.76 (95% CI 0.75 to 0.85) and 0.416 (95% CI 0.26 to 0.55), respectively. Serum miR-125b showed a statistically signiﬁcant difference between preoperative and postoperative patients in surgical patient groups (P = 0.003). Serum miR-125b levels were lower in patients with chemoresistance than that in patients with chemosensitivity (P < 0.0001). Serum miR-125b in combination with serum CA125 improved both sensitivity and speciﬁcity in diagnosis of EOC (P < 0.001). This study demonstrated that serum miR-125b levels were a useful diagnostic biomarker and biomarker to predict the responses to chemotherapy in patients with EOC.